Reviews (New blackfriars, 1966)
GRACE VERSUS NATURE: Studies in Karl Barth's Church Dogmatics BELIEF AND UNBELIEF: A PHILOSOPHY OF SELF-KNOWLEDGE by Michael Novak USES OF SOCIOLOGY. Edited by J. D. Halloran and Joan Brothers. THE SOCIOLOGY OF RELIGIOUS BELONGING by Hervé Carrier. PURITY AND DANGER by Mary Douglas. THE NATURE OF PSYCHOLOGY BIOLOGY AND PERSONALITY THE SAMARITANS. RELIGIOUS CONTROVERSIES OF THE NINETEENTH CENTURY. A HOUSE OF KINGS. The History of Westminster Abbey. MEDIEVAL LATIN AND THE RISE OF EUROPEAN LOVE-LYRIC